Empowerment Program Strategies to Improve the Economy of the Parit Banjar Village Community in Mempawah Subdistrict, Mempawah Regency - Rosiyeh, Rosiyeh; Prastyo, Heri (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to analyze the economic empowerment program for the Parit Banjar Village community as an effort to increase community income. The research is classified as descriptive qualitative research which examines problems with in-depth analysis, by collecting data through in-depth observation, interviews with related communities, and documentation as supporting data in the research. The results of the research show that this research shows that the Empowerment Program Strategy in Efforts to Improve the Economy of the Parit Banjar Village Community, Mempawah District, Mempawah Regency has a program as an empowerment strategy, this is shown in the form of training for the Parit Banjar Village community to increase the community's economic capacity and ability, apart from that of the Village community. Parit Banjar also received adequate infrastructure development as an empowerment program. Furthermore, the people of Parit Banjar Village emphasized the MSME economy as an empowerment effort resulting from community training and the development of community entrepreneurial groups so that the community could improve the economy well.